Indonesian Teachers’ Perceptions of Their School Well-being Based on Konu-Rimpela Model. - Rudy Yuniawati; Nurul Hidayah; Qi Lidong (Universitas Mercu Buana Yogyakarta, 2026)
This study was conducted to address the limited qualitative evidence on teachers’ perceptions of school well-being. It aims to explore these perceptions through key indicators of school well-being, specifically having, loving, being, and health status. Employing an evaluative qualitative design, the research sought to understand the psychological processes underlying teachers’ well-being within the school environment. A total of 16 teachers from two private middle schools in Sleman Regency, Indonesia, were selected through purposive sampling. Eligibility criteria included at least 1 year of teaching experience and active participation in school activities. Data were collected through focus group discussions (FGDs) guided by an interview protocol aligned with the school well-being indicators. Thematic analysis was used to identify key patterns across participants’ responses. The findings indicate that teachers perceive school well-being as encompassing both strengths and challenges across its various dimensions. Dissatisfaction was reported in the having dimension due to inadequate physical school environments. The loving dimension was reflected in positive interpersonal relationships alongside academic pressures stemming from remedial demands. In the being dimension, teachers felt meaningfully involved in school policies, and students actively participated in creative activities. The health dimension was evaluated as satisfactory. These findings highlight the importance of improving physical facilities, managing academic pressures, and strengthening participatory school practices to enhance both teacher and student well-being. Overall, teachers perceive school well-being as strong in interpersonal relationships, participation, and health, but weakened by inadequate physical environments. This result highlights the need for targeted interventions to improve teacher well-being, foster a more positive learning climate, and achieve better educational outcomes.